Polycarbonate / cellulose acetate blended ultrafiltration membrane as well as preparation method and application thereof
Through the preparation of polycarbonate/cellulose acetate blended ultrafiltration membrane materials, the problem of easy damage to existing ultrafiltration membrane materials in complex water quality is solved, efficient permeability, good hydrophilicity and mechanical properties are achieved, and the water treatment effect and service life are improved.
Patent Information
- Application Number
- CN202411925191.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
Existing ultrafiltration membrane materials are prone to mechanical damage, chemical degradation or biodegradation in complex water quality, resulting in short service life and high cost, and the adhesion of macromolecular substances or microorganisms leads to a decrease in flux and a decrease in separation effect.
The ultrafiltration membrane material is blended with polycarbonate/cellulose acetate, and the ultrafiltration membrane is prepared by blending the cast membrane liquid and using the NIPS method to form a membrane material with high efficiency permeability, good hydrophilicity and mechanical properties.
It achieves higher permeability, better hydrophilicity and mechanical properties, extends the service life of the membrane, reduces production costs, and improves the water treatment effect.
Smart Images

Figure CN119733392A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment materials and polymer membrane materials, and specifically discloses a polycarbonate / cellulose acetate blended ultrafiltration membrane and a preparation method and application thereof. Background Art
[0002] With the rapid development of industrialization and urbanization, water pollution has become increasingly serious, making efficient purification and sustainable use of water resources particularly important. Ultrafiltration technology is widely used in the field of water treatment because of its environmental friendliness, low energy consumption, large water output, and high separation accuracy. It can not only effectively filter out finer particulate matter and microorganisms, but also better remove certain soluble organic matter, thereby achieving a higher water purification effect. Research on the application of ultrafiltration membrane technology is not only crucial to promoting technological innovation and development in the field of water treatment, but also the key to ensuring public drinking water safety and achieving sustainable management of water resources.
[0003] However, challenges in ultrafiltration membrane technology still exist. On the one hand, long-term exposure to complex water quality can easily cause mechanical damage, chemical degradation or biological degradation of membrane materials, which reduces their service life and increases costs. On the other hand, macromolecules or microorganisms in complex water environments adhere to the membrane surface and precipitate in the membrane pores, causing problems such as decreased membrane flux and reduced separation effect. Therefore, choosing more durable and lower-cost membrane materials and taking simple methods to improve the membrane surface structure or hydrophilicity are issues that need to be addressed in the current water treatment field.
[0004] Bisphenol A polycarbonate, commonly known as polycarbonate (PC), is a chain polymer material and one of the five general engineering plastics. It is widely used in various fields of production and life. It has low production cost and is very easy to obtain. The benzene ring and -C=O bond in the PC structure provide it with many excellent properties, such as excellent mechanical strength, high heat resistance, and chemical resistance. At the same time, the -CO bond makes PC have a certain flexibility. Therefore, PC is considered to be a good candidate for membrane materials. However, the poor hydrophilicity and low porosity of PC have hindered its further development in the field of water treatment.
[0005] At the same time, cellulose acetate (CA) is one of the most important organic esters in cellulose and can be obtained by acetylation of cellulose. Due to its wide source, environmental friendliness and good hydrophilicity, CA has been widely used in fabrics, filtration membrane materials and other fields. However, CA ultrafiltration membrane materials also have disadvantages such as poor mechanical properties.
[0006] Therefore, for the two important polymer raw materials PC and CA, developing ultrafiltration membrane water treatment materials with high hydrophilicity, good permeability, good mechanical properties and simple preparation methods has become a key issue that researchers need to solve urgently. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a polycarbonate / cellulose acetate blended ultrafiltration membrane material and a preparation method thereof to address the problems existing in the prior art. The material combines the dual advantages of polycarbonate and cellulose acetate, exhibits high permeability, good hydrophilicity and mechanical properties, has a typical asymmetric porous structure, and the pore structure becomes more ordered.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The first object of the present invention is to provide a method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane, which specifically comprises the following steps:
[0010] (1) Polycarbonate / cellulose acetate blend casting solution: Cellulose acetate (CA) is dissolved in N-methylpyrrolidone (NMP) solvent or other organic solvents, and then porogen polyvinylpyrrolidone (PVP K30) is added and stirred magnetically until dissolved. Finally, polycarbonate particles (PC) are added and stirred until completely dissolved, and the mixture is allowed to stand for defoaming to obtain a casting solution.
[0011] (2) Preparation of ultrafiltration membrane (CPCM) by NIPS method: Before membrane preparation, the casting liquid obtained in step (1) is subjected to ultrasonic treatment; when preparing the membrane, an appropriate amount of casting liquid is poured onto a dry and flat glass plate, and a thin layer of liquid film is uniformly scraped out with a scraper, and then the glass plate with the liquid film is immersed in ultrapure water, and the liquid film is waited for to solidify and fall off the glass plate, and then transferred to clean ultrapure water for immersion, during which the water is changed every once in a while.
[0012] (3) Ultrafiltration membrane storage: Prepare a glycerol aqueous solution and store the membrane material prepared in step (2) therein.
[0013] Optionally, in step (1), the total mass of the casting liquid is 18 g, 0.5% to 2% by mass of cellulose acetate (CA) is dissolved in 83% by mass of N-methylpyrrolidone (NMP) or other organic solvents, then 1% by mass of a porogen polyvinylpyrrolidone (PVP K30) is added, and magnetic stirring is performed until dissolved, and finally 14% to 17% by mass of polycarbonate particles (PC) are added and stirred until completely dissolved.
[0014] Furthermore, in step (1), cellulose acetate and polyvinyl pyrrolidone are dissolved in N-methylpyrrolidone (NMP) or other solvents and stirred at 300 to 500 r·min -1 Stir with magnetic force until dissolved. When the polycarbonate particles are dissolved, adjust the magnetic stirring speed to 500-700 r / min. -1; Let the casting solution stand at room temperature for 10 to 13 hours for degassing.
[0015] It should be noted that in step (2), before film formation, the casting solution is subjected to ultrasonic treatment for 15-30 minutes to completely eliminate bubbles that may exist in the casting solution.
[0016] Optionally, in step (2), when making the film, pour the casting liquid on a dry and flat glass plate, the casting liquid should be spread out in long strips, and then use a scraper to scrape out a thin liquid film at a uniform speed with a thickness of 200 μm. The liquid film is exposed to the air for 10-15 seconds, and then the glass plate with the liquid film is immersed in ultrapure water, waiting for the liquid film to solidify and gradually fall off the glass plate.
[0017] Furthermore, in step (2), the solidified new membrane is transferred to clean ultrapure water and immersed for 24 hours to completely remove the residual solvent in the membrane. During this period, the water is changed every 12 hours.
[0018] Optionally, in step (3), a 30% glycerol aqueous solution is prepared and the membrane material is stored therein to protect the structure of the membrane from being damaged to the greatest extent.
[0019] The second object of the present invention is to provide a polycarbonate / cellulose acetate blended ultrafiltration membrane CPCM prepared by the method as described above. Compared with the pure polycarbonate ultrafiltration membrane, the finger-like pore structure of the blended ultrafiltration membrane becomes more ordered, and the hydrophilicity, mechanical properties and permeability are significantly improved.
[0020] The third object of the present invention is to provide a polycarbonate / cellulose acetate blended ultrafiltration membrane CPCM prepared by the method as described above and its application in the field of water treatment.
[0021] Furthermore, the polycarbonate / cellulose acetate blended ultrafiltration membrane CPCM can be used in a variety of water treatment applications such as seawater desalination, industrial wastewater, agricultural irrigation, and environmental protection.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention prepares a polycarbonate / cellulose acetate blended ultrafiltration membrane by blending cellulose acetate with polycarbonate, which has the advantages of simple preparation method, low cost, low energy consumption and good stability; at the same time, it combines the dual advantages of polycarbonate and cellulose acetate, exhibits high permeability, good hydrophilicity and mechanical properties, can achieve the purpose of separation and purification, and has great potential application prospects in the fields of seawater desalination, sewage treatment, rainwater collection and treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0025] Figure 1 2 are SEM images of the membrane materials in Comparative Example 1 and Example 1.
[0026] Figure 2 The water contact angle data of CPCM prepared with different amounts of cellulose acetate added in the examples are shown in FIG.
[0027] Figure 3 The pure water flux of CPCM prepared with different amounts of cellulose acetate added in the examples.
[0028] Figure 4 is the average pore radius of CPCM prepared with different amounts of cellulose acetate added in the examples.
[0029] Figure 5 The mechanical property data of CPCM prepared with different amounts of cellulose acetate added in the examples. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0032] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0033] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0034] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0035] The embodiment of the invention discloses a method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane with high hydrophilicity and good permeability.
[0036] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0037] Below, further description will be given in combination with specific embodiments and some raw material information involved.
[0038] Bisphenol A polycarbonate: purchased from Covestro Polymers Co., Ltd.
[0039] Polyvinyl pyrrolidone: purchased from Nantong Jingwei Biotechnology Co., Ltd.;
[0040] N-Methylpyrrolidone: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0041] Cellulose acetate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0042] Example 1: A method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane
[0043] (1) Prepare a polycarbonate / cellulose acetate blend casting solution with a total mass of 18 g. Dissolve 0.5% cellulose acetate in 83% N-methylpyrrolidone solvent, then add 1% porogen polyvinylpyrrolidone at 300 r / min. -1 Stir magnetically until dissolved, and finally add 15.5% polycarbonate particles (PC) and adjust the magnetic stirring speed to 700 r / min. -1 Stir until completely dissolved; let the casting solution stand at room temperature for 13 hours for degassing.
[0044] (2) Before film formation, the casting liquid was ultrasonically treated for 30 min. During film formation, the casting liquid was poured onto a dry and flat glass plate. The casting liquid should be spread into long strips. A thin liquid film with a thickness of 200 μm was uniformly scraped out with a scraper. The liquid film was exposed to the air for 10 s. The glass plate with the liquid film was then immersed in ultrapure water. The liquid film was allowed to solidify and gradually fall off the glass plate. The solidified new film was transferred to clean ultrapure water and soaked for 24 h to completely remove the residual solvent in the film. During this period, the water was changed every 12 h.
[0045] (3) Prepare a 30% glycerol aqueous solution and store the membrane material therein.
[0046] It should be noted that Figure 1 (b) is the SEM image of CPCM1, which is the sample of Example 1. Figure 2 CPCM1 is the water contact angle diagram of the sample in Example 1, Figure 3 CPCM1 is the pure water flux diagram of the sample in Example 1, Figure 4 CPCM1 is the average pore radius diagram of the sample in Example 1, Figure 5 CPCM1 is the mechanical properties diagram of the sample in Example 1.
[0047] Example 2: A method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane
[0048] (1) Prepare a polycarbonate / cellulose acetate blend casting solution with a total mass of 18 g. Dissolve 1% cellulose acetate in 83% N-methylpyrrolidone solvent, then add 1% porogen polyvinylpyrrolidone at 350 r / min. -1 Stir magnetically until dissolved, and finally add 15% polycarbonate particles (PC) by mass and adjust the magnetic stirring speed to 600 r·min -1 Stir until completely dissolved; let the casting solution stand at room temperature for 12 hours for degassing.
[0049] (2) Before film formation, the casting liquid was subjected to ultrasonic treatment for 25 min. During film formation, the casting liquid was poured onto a dry and flat glass plate. The casting liquid should be spread into long strips. A thin liquid film with a thickness of 200 μm was uniformly scraped out with a scraper. The liquid film was exposed to the air for 10 s. The glass plate with the liquid film was then immersed in ultrapure water. The liquid film was allowed to solidify and gradually fall off the glass plate. The solidified new film was transferred to clean ultrapure water and soaked for 24 h to completely remove the residual solvent in the film. During this period, the water was changed every 12 h.
[0050] (3) Prepare a 30% glycerol aqueous solution and store the membrane material therein.
[0051] It should be noted that Figure 2 CPCM2 is the water contact angle diagram of the sample in Example 2, Figure 3 CPCM2 is the pure water flux diagram of the sample in Example 2, Figure 4 CPCM2 is the average pore radius diagram of the sample in Example 2, Figure 5 CPCM2 is the mechanical properties diagram of the sample in Example 2.
[0052] Example 3: Preparation method of polycarbonate / cellulose acetate blended ultrafiltration membrane
[0053] (1) Prepare a polycarbonate / cellulose acetate blend casting solution with a total mass of 18 g. Dissolve 1.5% cellulose acetate in 83% N-methylpyrrolidone solvent, then add 1% porogen polyvinylpyrrolidone at 400 r / min. -1 Stir magnetically until dissolved, and finally add 14.5% polycarbonate particles (PC) and adjust the magnetic stirring speed to 550 r·min -1 Stir until completely dissolved; let the casting solution stand at room temperature for 11 hours for degassing.
[0054] (2) Before film formation, the casting liquid was ultrasonically treated for 20 min. During film formation, the casting liquid was poured onto a dry and flat glass plate. The casting liquid should be spread into long strips. A thin liquid film with a thickness of 200 μm was uniformly scraped out with a scraper. The liquid film was exposed to the air for 10 s. The glass plate with the liquid film was then immersed in ultrapure water. The liquid film was allowed to solidify and gradually fall off the glass plate. The solidified new film was transferred to clean ultrapure water and soaked for 24 h to completely remove the residual solvent in the film. During this period, the water was changed every 12 h.
[0055] (3) Prepare a 30% glycerol aqueous solution and store the membrane material therein.
[0056] It should be noted that Figure 2 CPCM3 is the water contact angle diagram of the sample in Example 3, Figure 3 CPCM3 is the pure water flux diagram of the sample in Example 3, Figure 4 CPCM3 is the average pore radius diagram of the sample in Example 3, Figure 5 CPCM3 is the mechanical properties diagram of the sample in Example 3.
[0057] Example 4: Preparation method of polycarbonate / cellulose acetate blended ultrafiltration membrane
[0058] (1) Prepare a polycarbonate / cellulose acetate blend casting solution with a total mass of 18 g. Dissolve 0.5% cellulose acetate in 83% N-methylpyrrolidone solvent, then add 1% porogen polyvinylpyrrolidone at 500 r / min. -1 Stir magnetically until dissolved, and finally add 15.5% polycarbonate particles (PC) and adjust the magnetic stirring speed to 500 r / min. -1 Stir until completely dissolved. Let the casting solution stand at room temperature for 10 hours for degassing.
[0059] (2) Before film formation, the casting liquid was subjected to ultrasonic treatment for 15 min. During film formation, the casting liquid was poured onto a dry and flat glass plate. The casting liquid should be spread into long strips. A thin liquid film with a thickness of 200 μm was uniformly scraped out with a scraper. The liquid film was exposed to the air for 10-15 s. The glass plate with the liquid film was then immersed in ultrapure water. The liquid film was allowed to solidify and gradually fall off the glass plate. The solidified new film was transferred to clean ultrapure water and soaked for 24 h to completely remove the residual solvent in the film. During this period, the water was changed every 12 h.
[0060] (3) Prepare a 30% glycerol aqueous solution and store the membrane material therein.
[0061] It should be noted that Figure 2 CPCM4 is the water contact angle diagram of the sample in Example 4, Figure 3 CPCM4 is the pure water flux diagram of the sample in Example 4, Figure 4 CPCM4 is the average pore radius diagram of the sample in Example 4, Figure 5 CPCM4 is the mechanical properties diagram of the sample in Example 4.
[0062] The content of the present invention is not limited to the content of the above embodiments. The combination of one or more embodiments can also achieve the purpose of the present invention.
[0063] Comparative Example 1: A method for preparing a polycarbonate ultrafiltration membrane
[0064] (1) Prepare a polycarbonate casting solution with a total mass of 18 g. Add 1% of the porogen polyvinyl pyrrolidone into 83% of the N-methyl pyrrolidone solvent at 300 r / min. -1 Stir magnetically until dissolved, and finally add 16% polycarbonate particles (PC) by mass and adjust the magnetic stirring speed to 700 r / min -1 Stir until completely dissolved; let the casting solution stand at room temperature for 14 hours for degassing.
[0065] (2) Before film formation, the casting liquid was ultrasonically treated for 30 min. During film formation, the casting liquid was poured onto a dry and flat glass plate. The casting liquid should be spread into long strips. A thin liquid film with a thickness of 200 μm was uniformly scraped out with a scraper. The liquid film was exposed to the air for 10 s. The glass plate with the liquid film was then immersed in ultrapure water. The liquid film was allowed to solidify and gradually fall off the glass plate. The solidified new film was transferred to clean ultrapure water and soaked for 24 h to completely remove the residual solvent in the film. During this period, the water was changed every 12 h.
[0066] (3) Prepare a 30% glycerol aqueous solution and store the membrane material therein.
[0067] It should be noted that Figure 1 (a) is the SEM image of the PCM sample of Comparative Example 1. Figure 2 PCM in the figure is the water contact angle diagram of the sample in comparative example 1. Figure 3 The PCM in the figure is the pure water flux diagram of the sample in comparative example 1. Figure 4 The PCM in the figure is the average pore radius diagram of the sample in comparative example 1. Figure 5 The PCM in the figure is the mechanical properties diagram of the sample in comparative example 1.
[0068] In order to further verify the excellent effect of the present invention, the inventors also conducted the following experiments:
[0069] Experiment 1: To illustrate the pore structure morphology of CPCM
[0070] In order to study the pore structure of CPCM, a scanning electron microscope (S-4800, Hitachi High-Technologies Corporation, Japan) was used to observe the cross-sectional structural morphology of the CPCM blend membrane in Example 1. The membrane was dried at room temperature and then fractured in liquid nitrogen.
[0071] Depend on Figure 1 From the SEM of the cross sections of PCM (a) and CPCM (b) in Comparative Example 1 and Example 1, it can be seen that CPCM has a more ordered asymmetric porous finger-like pore structure, which enables it to have a high water flux.
[0072] Experiment 2: To illustrate the hydrophilicity of CPCM
[0073] In order to evaluate the hydrophilicity of CPCM, the water contact angle of the membrane surface was measured by a contact angle meter (SL200KB, Shanghai Solon Technology Information Co., Ltd.). The membrane sample in the example needs to be tested 3 times at different positions.
[0074] Depend on Figure 2 It can be seen that the addition of cellulose acetate can significantly increase the hydrophilicity of CPCM.
[0075] Experiment 3: To illustrate the permeability performance of CPCM
[0076] In order to study the permeability performance of CPCM, a cross-flow ultrafiltration device (UFMT-01, Shengtuo Mingke Experimental Instrument Business Department) was used for testing. After the membrane in the embodiment was placed in the membrane chamber, the membrane was pre-pressed with pure water at 0.3MPa for 0.5h, and then the time required to collect a certain volume of permeate was recorded to calculate the pure water flux of the membrane.
[0077] Depend on Figure 3 It can be seen that cellulose acetate can significantly increase the pure water flux of CPCM.
[0078] Experiment 4: Average hole radius for CPCM
[0079] In order to study the pore size of CPCM, the porosity of the membrane material in the embodiment was calculated by weighing method, and then the average pore radius of the membrane was calculated according to the pure water flux and porosity of the membrane in the embodiment.
[0080] Depend on Figure 4 It can be seen that cellulose acetate can significantly increase the pore size of CPCM.
[0081] Experiment 5: To illustrate the mechanical properties of CPCM
[0082] In order to study the mechanical properties of CPCM, an electronic universal testing machine (TSE104B, Shenzhen Wance Testing Equipment Co., Ltd.) was used for testing. The membrane was dried at room temperature and then cut into 1.5 cm × 12 cm membrane sheets. Before measurement, the distance between the test machine fixtures was adjusted to 100 mm and the tensile speed was adjusted to 5 mm min -1 .
[0083] Depend on Figure 5 It can be seen that cellulose acetate can increase the softness of CPCM.
[0084] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane, characterized in that: The following steps are involved: (1) dissolving cellulose acetate (CA) in an organic solvent, then adding a porogen polyvinyl pyrrolidone (PVP K30), stirring magnetically until dissolved, and finally adding polycarbonate particles (PC) and stirring until completely dissolved, and standing to defoam to obtain a casting solution; (2) Before film formation, the casting liquid is subjected to ultrasonic treatment; during film formation, the casting liquid is poured onto a dry and flat glass plate, and a thin layer of liquid film is uniformly scraped out with a scraper, and then the glass plate with the liquid film is immersed in ultrapure water, and the liquid film is waited for to solidify and fall off the glass plate, and then transferred to clean ultrapure water for immersion, and the water is changed every once in a while; (3) Prepare a glycerol aqueous solution and store the membrane material therein.
2. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 1, characterized in that: In the step (1), the total mass of the casting liquid is 18 g, 0.5% to 2% of cellulose acetate (CA) is dissolved in 83% of an organic solvent, then 1% of a porogen polyvinyl pyrrolidone (PVP K30) is added, and magnetic stirring is performed until dissolved, and finally 14% to 17% of polycarbonate particles (PC) are added and stirred until completely dissolved.
3. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 1 or 2, characterized in that: In the step (1), cellulose acetate and polyvinyl pyrrolidone are dissolved in an organic solvent and heated at 300 to 500 r / min. -1 Stir magnetically until dissolved, add polycarbonate particles and adjust the magnetic stirring speed to 500-700 r / min -1 ; Let the casting solution stand at room temperature for 10 to 13 hours for degassing.
4. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 1, characterized in that: In the step (2), before forming the membrane, the casting solution is subjected to ultrasonic treatment for 15-30 minutes.
5. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 1 or 4, characterized in that: In the step (2), when making the film, pour the casting liquid on a dry and flat glass plate. The casting liquid should be spread into long strips, and then use a scraper to scrape out a thin liquid film at a uniform speed with a thickness of 200 μm. The liquid film is exposed to the air for 10-15 seconds, and then the glass plate with the liquid film is immersed in ultrapure water, waiting for the liquid film to solidify and gradually fall off the glass plate.
6. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 5, characterized in that: In the step (2), the solidified new membrane is transferred to clean ultrapure water for immersion, during which the water is changed every 12 hours.
7. The method for preparing a polycarbonate / cellulose acetate blended ultrafiltration membrane according to claim 1, characterized in that: In the step (3), a 30% glycerol aqueous solution is prepared.
8. A polycarbonate / cellulose acetate blend ultrafiltration membrane prepared by the method of claim 1.
9. Use of a polycarbonate / cellulose acetate blended ultrafiltration membrane prepared by the method of claim 1 in the field of water treatment.
Citation Information
Patent Citations
Processing technology of polyacrylic acid and cellulose acetate composite membrane
CN101007241A
Hydrophilic film material and preparation method thereof
CN101773789A
Composite nuclear track membrane and preparation method thereof
CN104001429A
Preparation method of polycarbonate composite film
CN117400462A
Polycarbonate ultrafiltration membrane as well as preparation method and application thereof
CN118558151A
Cited By
Thin-layer composite ultrafiltration membrane as well as preparation method and application thereof
CN120644081A
Zinc-containing cellulose-based carboxylic ester as well as preparation and application thereof
CN121181716A
Lignocellulose or cellulose sulfonate ether as well as preparation and application thereof
CN121293379A